Budgeting in Turkey - Kraan, Dirk-Jan (OECD Publishing, 2007)
The Turkish budget process has three features which set it apart from other OECD countries: a centralised yet fragmented decision-making process; the IMF stand-by agreement as a de facto fiscal rule; and a very detailed line-item classification. This article analyses these features and makes suggestions for policy adjustment to improve effectiveness and efficiency. The article examines all stages of the budget process (preparation, parliamentary approval, execution, and accounting and auditing) and assesses Turkey's recent rapid progress with reform. The article offers suggestions for next steps and new priorities for Turkey in the light of other OECD country experience